Three new species of Xyris (Xyridaceae) from the Espinhaço Range, Brazil - Wanderley, Maria Das Graças Lapa; Mota, Nara F. O. (Phytotaxa, 2015)
Three new species of Xyris from Brazil are described and illustrated. Xyris nevata is characterized by bracts with conspicuous veins and a reddish androecium and gynoecium; X. pulchella also exhibits a reddish androecium and gynoecium, and is further characterized by its small size and terete to subterete leaf blades; X. rostrata has a turbinate spike and bracts with a rostrate-acuminate apex. Commentary is provided for each species on habitat, distribution, phenology and conservation status, and the new species are compared with morphologically similar species.